Synthesis of 1-butoxy-4-tert-butylbenzene under The Effect of Multi-site Phase Transfer Catalysis System – A Kinetic Study - Manickam Sathiyaraj; Perumal Venkatesh (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Phase transfer catalysis technique proved to be a useful method for synthesizing various organic compounds under heterogeneous reactions and recognized as a viable environmentally friendly. The influence of a new multi site phase transfer catalyst (MPTC) is the synthesis of 1-butoxy-4-tertbutylbenzene from 4-tert-butylphenol with 1-bromobutane (BB) under heterogeneous solid-liquid condition using potassium hydroxide as a base at 60 °C. The higher conversion of 1-bromobutane was achieved by using the synergistic condition of multi-site phase transfer catalyst in better efficacy. The reaction rate enhanced by decreases the volume of water. The apparent the reaction rate was found to be pseudo-first order kinetics. The apparent rate constant was increased linearly with the increase in the concentration of various parameters, such as: MPTC, temperature, potassium hydroxide, and stirring speed. The activation energy (Ea) was also calculated through the Arrhenius plot. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).